Analisis Komparatif Buku Teks Bahasa Indonesia Kelas VIII: "Bahasa Indonesia" (Grafindo, Kurikulum Merdeka) dan "Piawai Berbahasa Indonesia" (Erlangga, Kurikulum 2013 Revisi) - Rosmawaty Rosmawaty; Alisya Putri Amelia; Siti Nur Wulandari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze in-depth the differences between two Indonesian language textbooks for Grade VIII SMP/MTs: "Bahasa Indonesia untuk SMP/MTS Kelas VIII" by Muhamad Zainal Arifin, published by Grafindo Media Pratama (Kurikulum Merdeka, 2023), and "Piawai Berbahasa Indonesia 2 untuk SMP/MTS Kelas VIII" by Nurhadi, Giri Indra K., and Maifan Tri S., published by Erlangga (Revised 2013 Curriculum). The method employed is content analysis with a descriptive-comparative approach. The analysis focuses on seven main aspects: (1) book identity and legality, (2) philosophical foundations and curriculum approaches, (3) material structure and organization, (4) types of texts and genres presented, (5) learning features and components, (6) assessment systems, and (7) contextual relevance and literacy development. The results indicate that both books are oriented toward text-based approaches and activity-based learning; however, they differ significantly in terms of competency frameworks, material depth, technology integration, and assessment design. The Grafindo book (Kurikulum Merdeka) emphasizes holistic learning outcomes per phase with multimedia integration and Minimum Competency Assessment (AKM) questions, while the Erlangga book (K-13) is more structured through Core and Basic Competencies (KI-KD) with systematic, step-by-step activity-based features. These findings are expected to serve as a scientific reference for teachers, school principals, and policymakers in selecting and implementing Indonesian language textbooks that best suit the context and needs of students.